Freedom of female sexuality in Calixthe Beyala's C'est le soleil qui m'a brûlée: a critical analysis in translation - Chomga, Annick Vanessa Magne (My University, 2016)
The study provides a comparative and contrastive analysis of Calixthe Beyala’s novel, C'est le soleil qui m'a brûlée, and its translation, The Sun Hath Looked upon Me, by Marjolijn de Jager focusing on textual, paratextual and metatextual elements of these two texts. The analysis shows how the translator dealt with the disruptive stylistic effects of a postcolonial text and the themes around which the novel is centred. Problems and solutions related to postcolonial translations and relevant theories are approached in the analysis. The textual analysis is done using Gérard Genette’s (1997) model of analysis of the elements of the paratext and Vinay and Darbelnet’s (1995) model of comparative analysis of French and English.
A research report submitted to the Faculty of Humanities, University of the Witwatersrand, Johannesburg, in partial fulfilment of the requirements for the degree of Master of Arts in Translation Johannesburg, March 2016
Keywords: Beyala, Calixthe--Criticism and interpretation; Beyala, Calixthe--Translations into English; Feminist literature--Africa; Translating and interpreting--Fiction; Discourse analysis--Methodology